1985
DOI: 10.1002/1097-0142(19850201)55:3<570::aid-cncr2820550316>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Malignant lymphoma and malignant angioendotheliomatosis: One disease

Abstract: A patient was diagnosed as having angioendotheliomatosis proliferans systemisata (APS) based on characteristic clinical and histologic features. A few days later, malignant lymphoma involving the gut was discovered. Immunohistochemical and electronmicroscopic studies confirmed the nonendothelial and lymphoid nature of intravascular tumor cells. This is the sixth case in which malignant lymphoma has been shown to involve the vessels of the skin (and probably of other organs) in a pattern identical to that seen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
59
0
8

Year Published

1986
1986
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(68 citation statements)
references
References 20 publications
1
59
0
8
Order By: Relevance
“…This entity was initially considered as an endothelial neoplasm, but with the advent of immunohistochemical studies, the lymphoid origin of this peculiar disease was established, imposing its reclassification as angioendotheliotropic lymphoma (Kiel), angiotropic large cell lymphoma (LukesCollins), and unclassified large B-cell lymphoma in the Revised European American Lymphoma (REAL) Classification [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…This entity was initially considered as an endothelial neoplasm, but with the advent of immunohistochemical studies, the lymphoid origin of this peculiar disease was established, imposing its reclassification as angioendotheliotropic lymphoma (Kiel), angiotropic large cell lymphoma (LukesCollins), and unclassified large B-cell lymphoma in the Revised European American Lymphoma (REAL) Classification [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Initially, this neoplasm had been believed to originate from the vascular endothelial cells because of its unique intravascular proliferative pattern [2,3]. In 1985, however, it was proved to derive from the B lymphocytes using immunohistochemical staining [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Ansell et al (5)suggested a lymphoid origin in 1982 by demonstrating surface Ig on the neoplastic cells. Subsequently, Bhawan et al (6) and Wrotnowski et al (7) reported leukocyte common antigen expression in 1985. The lymphoid nature was confirmed by Wick et al (8) in 1986.…”
mentioning
confidence: 99%